Exploring the Nuclear Fuel Cycle: Highlights and Innovations (Brazilian Journal of Radiation Sciences (BJRS), 2024)
The paper thoroughly covers the nuclear fuel cycle, a complex and vital process in energy generation through uranium fission. The cycle comprises various stages, from uranium extraction and processing to its use as fuel material in nuclear reactors. This work primarily aims to highlight the peculiarities and innovations of the nuclear fuel cycle in the Brazilian context, seeking to promote academic and commercial interest and drive research and investments in this strategic area. The research conducted to underpin this work was comprehensive, involving literature reviews, technical visits, and discussions with specialized professionals. The conclusion emphasizes the relevance of the nuclear fuel cycle and how this work intends to highlight its specificities, underscoring the importance of this cycle for Brazil as a source of clean and safe energy generation.